The Impact of Work Environment, Instrumentality Beliefs, Perceived Labor Union Image, and Subjective Norms on Union Voting Intentions - Youngblood, Stuart A.; DeNisi, Angelo S.; Molleston, Julie L.; Mobley, William H. (Academy of Management Journal, 1984)
A model of the unionization process is proposed, tested, and generally supported. The constructs of work environment, instrumentality beliefs, and labor union image are hypothesized as trigger, augmenter, and veto influences, respectively, of pro union voting intentions. In addition, the role of referent others is hypothesized to be a determinant of pro union voting intention.